Studies on Raschel knotless Netting - NAYAR, S GOPALAN; RADHALAKSHMI, K (Fishery Technology, 2017)
Production of knotless webbings is of recent origin in India. An attempt has been made to evaluate the quality of the product consequent to its introduction in the fishing indus.try. A method has been presented to fix up yarn specification for Rasche! knotless nettings equivalent to a given knotted netting.